Experimental micromechanics: grain-scale observation of sand deformation. Issue 3 (28th September 2012) - Andò, E.; Hall, S. A.; Viggiani, G.; Desrues, J.; Bésuelle, P.
Abstract : Strain localisation plays a key role in the deformation of granular materials. Such localisation involves bands of just a few grains wide, which dominate the material's macroscopic response. This grain-scale phenomenon presents challenges for continuum modelling, which is the rationale behind models that explicitly take micro-scales into account. These in turn require micro-scale experimental analysis. In this work, X-ray tomography is used to image a small sample of oolitic sand while it deforms under triaxial compression. Grains are followed with a technique combining recent developments in image correlation and particle tracking. From these rich data, the evolution of the material in a subvolume of a thousand grains inside the sample (which contains 53 000 grains) is presented. The subvolume is chosen to lie inside the shear band that appears at the sample scale. Three-dimensional (3D) grain kinematics are analysed in three increments: the beginning of the test, the peak of the sample's macroscopic axial stress response and the residual stress state. When the sample's deformation is homogeneous (increment one) or fully localised (increment three), the kinematics of the grains in the subvolume appear to be representative of the kinematics occurring at the sample scale, allowing micro-mechanical observations to be made. In the transition from homogeneous to localised deformation (increment two), however, the scale of observation requires a zoom out of the subvolume to the sample scale in order to capture the complex mechanisms at play.